3 x 2 3 1 4 x 3 4 1 2 x 1 3 3 x 2 1 4 4 x 3 7f x i 1 n i x 1 i f x x 2 x 1 2 3

3 x 2 3 1 4 x 3 4 1 2 x 1 3 3 x 2 1 4 4 x 3 7f x i 1

This preview shows page 25 - 31 out of 78 pages.

3 x 2 3 + 1 4 x 3 4 = 1 2 x + 1 3 3 x 2 + 1 4 4 x 3 7) f ( x ) = i = 1 n i x 1 i f ( x ) = x + 2 x 1 2 + 3 x 1 3 + 4 x 1 4 + ... + n x 1 n df dx = 1 + 2 1 2 x 1 2 + 3 ¿ 1 3 x 2 3 + 4 1 4 x 3 4 + ... + n 1 n x 1 n n df dx = 1 + x 1 2 + x 2 3 + x 3 4 + ... + x 1 n n df dx = i = 1 n x 1 i i 8) ¿ r 2 + 1 ¿ ¿ r ¿ 7 r 3 ¿ u ( r ) = ¿ ¿ r ¿ 7 r 7 7 r 7 1 ( r 3 ) ' ( r 2 + 1 ) r 3 ( r 2 + 1 ) ' ( r 2 + 1 ) 2 du dr = ¿ ¿ r ¿ 6 r ¿ r 7 7 r 6 3 r 2 ( r 2 + 1 ) r 3 2 r ( r 2 + 1 ) 2 ¿ du dr = ¿ ¿ r ¿ r 3 r 4 + 3 r 2 2 r 4 ( r 2 + 1 ) 2 ¿ r ¿ 6 ¿ du dr = 7 ¿ ¿ r ¿ r 3 r 2 + r 4 ( r 2 + 1 ) 2 ¿ r ¿ 6 ¿ du dr = 7 ¿
Image of page 25
9) g ( t ) = t 5 + t 4 7 t 4 + t 1 6 du dr = ( 5 t 4 + 4 7 t 4 7 1 ) ( t 4 + t 1 6 ) ( t 5 + t 4 7 ) ( 4 t 3 + 1 6 t 5 6 ) ( t 4 + t 1 6 ) 2 du dr = ( 5 t 4 + 4 7 t 3 7 ) ( t 4 + t 1 6 ) ( t 4 + t 1 6 ) 2 ( t 5 + t 4 7 ) ( 4 t 3 + 1 6 t 5 6 ) ( t 4 + t 1 6 ) 2 du dr = 5 t 4 + 4 7 t 3 7 t 4 + t 1 6 ( t 5 + t 4 7 ) ( 4 t 3 + 1 6 t 5 6 ) ( t 4 + t 1 6 ) 2 10) h ( s ) = 4 s 5 4 + 7 s 6 6 s 6 + 7 5 dh ( s ) ds = 4 ( 5 4 ) s 5 4 1 + 7 ( 6 s 5 ) ( 6 s 7 + 7 ) 7 s 6 ( 6 7 s 6 ) ( 6 s 7 + 7 ) 2 dh ( s ) ds = 5 s 1 4 + 252 s 12 + 294 s 5 294 s 12 ( 6 s 7 + 7 ) 2 dh ( s ) ds = 5 s 1 4 + 294 s 5 425 s 12 ( 6 s 7 + 7 ) 2 11) u ( x ) = | x 2 x | du dx = | x 2 x | x 2 x ( 2 x 1 ) 12) v ( x ) = | x 5 1 | + | x | x 2 + 5 x dv ( x ) dx = ( | x 5 1 | + | x | x 5 1 5 x 4 + | x | x ) ( x 2 + 5 x ) ( | x 5 1 | + | x | ) ( 2 x + 5 ) ( x 2 + 5 x ) 2
Image of page 26
dv ( x ) dx = | x 5 1 | + | x | x 5 1 5 x 4 + | x | x x 2 + 5 x ( | x 5 1 | + | x | ) ( 2 x + 5 ) ( x 2 + 5 x ) 2
Image of page 27
4.2 Derivada aplicando la definición 1) y = x + x 2 f ( x ) = x + x 2 y ' = lim h→ 0 f ( x + h ) f ( x ) h f ( x + h ) = x + h + ( x + h ) 2 y ' = lim h→ 0 x + h + ( x + h ) 2 x x 2 h y ' = lim h→ 0 h + x 2 + 2 xh + h 2 x 2 h = lim h→ 0 h ( 1 + 2 x + h ) h y ' = 1 + 2 x 2) y = 2 x + 3 x 3 f ( x ) = 2 x + 3 x 3 y ' = lim h→ 0 f ( x + h ) f ( x ) h f ( x + h ) = 2 ( x + h ) + 3 ( x + h ) 3 y ' = lim h→ 0 2 x + 2 h + 3 ( x 3 + 3 x 2 h + 3 x h 2 + h 3 ) 2 x 3 x 3 h y ' = lim h→ 0 2 h + 3 x 3 + 9 x 2 h + 9 x h 2 + 3 h 3 3 x 3 h y ' = lim h→ 0 h ( 9 x 2 + 9 xh + 3 h 2 + 2 ) h = 9 x 2 + 2 3) y = a x + x f ( x ) = a x + x y ' = lim h→ 0 f ( x + h ) f ( x ) h f ( x + h ) = a x + h + x + h y ' = lim h→ 0 a x + h + x + h a x x h + h h = lim h→ 0 a x + h a x h + h h = lim h→ 0 a x ( a h 1 ) h + 1 lim h→ 0 ( a h 1 ) h a x lim z→ 0 z a x ln | 1 + z | lna = lna lim z→ 0 1 ln | 1 + z | z a x a h 1 = z ¿ lna lim z→ 0 1 ln | 1 + z | 1 z a x
Image of page 28
a h = 1 + z ¿ lna lim z→ 0 a x ln | lim z→ 0 ( 1 + z ) 1 z | = lna lne a x h lna = ln | 1 + z | y ' = a x ln a + 1 h = ln | 1 + z | lna 4) y = senx + e x f ( x ) = senx + e x y ' = lim h→ 0 f ( x + h ) f ( x ) h f ( x + h ) = sen ( x + h ) + e x h y ' = lim h→ 0 sen ( x + h ) + e x h senx e x h y ' = lim h→ 0 sen ( x + h ) senx h + lim h→ 0 e x e h e x h y ' = lim h→ 0 senx cosh cosx senh senx h + e x lim h→ 0 e h 1 h y ' = lim h→ 0 senx + cosx senh senx h + e x ( lne ) ( Por lo calculado en el anterior ejemplo ) y ' = lim h→ 0 senh h cosx e x y ' = cosx e x 5) y = tgx f ( x ) = tgx y ' = lim h→ 0 tg ( x + h ) tg ( x ) h f ( x + h ) = tg ( x + h ) y ' = lim h→ 0 sen ( x + h ) h cos ( x + h ) senx h cos x y ' = lim h→ 0 sen ( x + h ) + e x h senx e x h cosh = cos 0 = 1 y ' = lim h→ 0 cosx ( senx cosh + cosx senh ) senx ( cosx cosh senx senh ) h cosx cos ( x + h ) y ' = lim h→ 0 cosx senx + cos 2 x senh senx cosx + sen 2 x senh hcosx cos ( x + h )
Image of page 29
y ' = lim h→ 0 senh h sen 2 x + cos 2 x cosx cos ( x + h ) = 1 cos 2 x = sec 2 x 6) y = lnx f ( x ) = lnx y ' = lim h→ 0 ln ( x + h ) ln ( x ) h f ( x + h ) = ln ( x + h ) y ' = lim h→ 0 ln ( x + h x ) h = lim h→ 0 ln ( 1 + h x ) 1 h y ' = lim h→ 0 ln ( 1 + h x ) 1 h x x = lim h→ 0 ln ( 1 + h x ) x h 1 x y ' = lim h→ 0 1 x ln ( 1 + h x ) x h = 1 x ln ( lim h→ 0 ( 1 + h x ) x h ) y ' = 1 x lne = 1 x 7) y = 3 x f ( x ) = 3 x y ' = lim h→ 0 3 x + h 3 x h f ( x + h ) = 3 x + h y ' = lim h→ 0 ( 3 x + h 3 x ) ( 3 ( x + h ) 2 + 3 x ( x + h ) + 3 x 2 ) h ( 3 ( x + h ) 2 + 3 x ( x + h ) + 3 x 2 ) y ' = lim h→ 0 ( 3 x + h ) 3 ( 3 x ) 3 h ( 3 ( x + h ) 2 + 3 x ( x + h ) + 3 x 2 ) =
Image of page 30
Image of page 31

  • Left Quote Icon

    Student Picture

  • Left Quote Icon

    Student Picture

  • Left Quote Icon

    Student Picture